Efektivitas Metode How to Become pada Pembelajaran Sesorah di SMK Al Mina Bandungan (Jurusan Bahasa dan Sastra Jawa Universitas Negeri Semarang, 2022)
School regulation at SMK Al Mina Bandungan regarding time management of the study and the students’ activities becomes a crucial thing for the teacher to determine effective learning methods. Based on the research background, this study aimed to assess the effectiveness of the “How to Become” method in sesorah learning at SMK Al Mina Bandungan. This study employed experimental research which used Quasi-Experimental Design as an approach to compare the two research groups which are not correlated. The data analysis used in this study were T-Test and N-Gain. The result of statistical analysis showed that the data from both the experimental group and control group were distributed normally and homogenous. After the study measurement, the T-Test result showed that there were no significant differences between those two groups. Whereas, the N-gain result showed that the pretest and post-test score improvements of the experimental group were higher than the control group with insignificant differences. According to the statistical report and some other factors, it can be concluded that the “How to Become” method is not effective for sesorah learning at SMK Al Mina Bandungan.